ASSOCIATION OF LIPID PROFILE WITH DEPRESSIVE FEATURES IN YOUNG HYPERTENSIVES - Gupta, Ravi; Solanki, Ram Kumar; Dubey, Vaibhav; Midha, Purav Kumar; Pathak, Vijay (Journal of Pakistan Psychiatric Society, 2008)
Objectives: To find out (a) the correlation of various components of serum lipids with depression score; (b) whether severity of depression differ between the people with normal serum lipids & dyslipidemia;and (c) whether the lipid components differ between depressed and non-depressed people. Design: Cross Sectional Cohort study. Place and duration of the study: This study was conducted at Sawai Man Singh Medical College and Hospital, Jaipur, India from January 2001 to June 2002. Subjects and Methods: 100 young primary hypertensive subjects were included in this study. Their fasting blood lipid profile was ascertained and their depressive feelings were rated with the help of HAM-D. Results: In this study, total lipids, high density lipoprotein, low density lipoprotein, very low density lipoproteins and triglycerides were positively correlated with the HAM D score. Depressed subjects (HAMD>17) had higher levels of total lipids (P=0.002), HDL (P=0.04), VLDL (P=0.02) and TG (P=0.001). Similarly subjects with higher cholesterol levels (P=0.05), normal HDL (P=0.003), normal LDL (P<0.001); higher VLDL (P=0.002) and higher TGs (P<0.001) had higher scores on HAM-D. Conclusions: This study suggests that low HDL, high LDL protects from the depression. On the other hand, high cholesterol, VLDL and TG increase the risk of depression. Key words: Hypertension, Young, Lipid profile, Depressive features.